2007
DOI: 10.1002/cm.20257
|View full text |Cite
|
Sign up to set email alerts
|

Building a radial spoke: Flagellar radial spoke protein 3 (RSP3) is a dimer

Abstract: Radial spokes are critical multisubunit structures required for normal ciliary and eukaryotic flagellar motility. Experimental evidence indicates the radial spokes are mechanochemical transducers that transmit signals from the central pair apparatus to the outer doublet microtubules for local control of dynein activity. Recently, progress has been made in identifying individual components of the radial spoke, yet little is known about how the radial spoke is assembled or how it performs in signal transduction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 48 publications
2
47
0
1
Order By: Relevance
“…Furthermore, the RIIa domains in RSP11 and RSP7, and the Dpy-30 domains in RSP2 and RSP23 (NDK5) in the stalk are dimerization and docking (DD) domains of striking similar tertiary structures . Finally, RSP3 that docks the RS to outer doublets also exists as a homodimer (Diener et al 1993;Wirschell et al 2008). RIIa-containing RSPs showed the physiological relevance of the binding of RSP3 to the RIla-containing RII in the cAMP-dependent protein kinase (PKA) (Gaillard et al 2001) in an in vitro assay credited for the discoveries of many PKA-anchoring proteins (AKAPs).…”
Section: Organization Of Rspsmentioning
confidence: 99%
“…Furthermore, the RIIa domains in RSP11 and RSP7, and the Dpy-30 domains in RSP2 and RSP23 (NDK5) in the stalk are dimerization and docking (DD) domains of striking similar tertiary structures . Finally, RSP3 that docks the RS to outer doublets also exists as a homodimer (Diener et al 1993;Wirschell et al 2008). RIIa-containing RSPs showed the physiological relevance of the binding of RSP3 to the RIla-containing RII in the cAMP-dependent protein kinase (PKA) (Gaillard et al 2001) in an in vitro assay credited for the discoveries of many PKA-anchoring proteins (AKAPs).…”
Section: Organization Of Rspsmentioning
confidence: 99%
“…In addition to its usefulness in studying plant biology, the biochemical similarity of Chlamydomonas flagella to mammalian cilia has made Chlamydomonas a leading model for elucidating cilia structure and function (Jarvik and Rosenbaum, 1980;Tam and Lefebvre, 1993;Li et al, 2004;Mitchell, 2004;Yang et al, 2006;Wirschell et al, 2008), with discoveries including the characterization of intraflagellar transport (Kozminski et al, 1993;Baldari and Rosenbaum, 2010). In addition, Chlamydomonas motility mutants have helped reveal the molecular basis for many human diseases that result from cilia dysfunction, such as polycystic kidney disease (Lewin, 1953;Mintz and Lewin, 1954;Pazour et al, 2000;Qin et al, 2001;Fliegauf et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it should be evolutionarily conserved, as the dimension of typical 9 + 2 axonemes is similar (Mastronarde et al, 1992;Pigino et al, 2011;Barber et al, 2012). Sequence analysis showed that among the 19 spoke components, the best candidate core protein is RSP3, the dimeric spoke AKAP (Gaillard et al, 2001;Wirschell et al, 2008;Diener et al, 2011), although experimental evidence positioned RSP3, in fact only its N-terminal 80-aa region, at the base of the RS, for binding the entire complex to the axoneme ( Fig. 2; Diener et al, 1993).…”
Section: Prediction Of the Riia Clan Anchoring Protein In The Rsmentioning
confidence: 99%
“…The spoke AKAP RSP3 and the RS proteins (RSPs) with a putative D/D domain appear to be involved in these central functions and are exclusively located in the spoke stalk. RSP3 AKAP operates as a homodimer (Wirschell et al, 2008). It is essential to the assembly of the entire complex and considered to be the spoke base, targeting RSs to axonemes (Williams et al, 1989;Diener et al, 1993).…”
Section: Introductionmentioning
confidence: 99%